WP4 : Mapping of stakeholders involved in agroecology in Burkina Faso - Dedieu, Claire (2023)
This document synthesizes different maps of actors involved in the development of agroecology in Burkina Faso. The gathering and synthesis of existing data on agroecology stakeholders has become a real challenge for the accumulation of knowledge. Research and development projects on agroecology have flourished in recent years, and several stakeholder maps have been produced, often as a prerequisite for the establishment of consultation frameworks between stakeholders.